1985
DOI: 10.1083/jcb.100.5.1558
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of multivesicular bodies from rat hepatocytes: an organelle distinct from secretory vesicles of the Golgi apparatus.

Abstract: ABSTR^Cr Hepatocytes of estradiol-treated rats, which express many low density lipoprotein receptors, rapidly accumulate intravenously injected low density lipoprotein in multivesicular bodies (MVBs). We have isolated MVBs and Golgi apparatus fractions from livers of estradioltreated rats. MVB fractions were composed mainly of large vesicles, ~0.55 tam diam, filled with remnantlike very low density lipoproteins, known to be taken up into hepatocytes by receptor-mediated endocytosis. MVBs also contained numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 72 publications
(89 reference statements)
1
39
1
Order By: Relevance
“…Cholesterol is also implicated in MVB biogenesis owing to its significant enrichment in MVBs (Hornick et al 1985). Analysis of exosomes reveals that much of the endosomal cholesterol resides in ILVs , Wubbolts et al 2003, although the levels of cholesterol within intralumenal membranes vary among cell types (Subra et al 2006).…”
Section: Machinery Lipid Sortingmentioning
confidence: 99%
“…Cholesterol is also implicated in MVB biogenesis owing to its significant enrichment in MVBs (Hornick et al 1985). Analysis of exosomes reveals that much of the endosomal cholesterol resides in ILVs , Wubbolts et al 2003, although the levels of cholesterol within intralumenal membranes vary among cell types (Subra et al 2006).…”
Section: Machinery Lipid Sortingmentioning
confidence: 99%
“…Similar particles observed in prelysosomal organelles of rat liver have been identified as remnants of TG-rich lipoproteins. 32 Compositional analysis of A-VLDL isolated from aortic tissue containing mild fatty streaks showed a lower TG-tocholesterol ratio (0.57) than plasma VLDL (4.35), and SDS gradient gel bands corresponding to apo A-I, apo B-100, and C apolipoproteins were seen (Fig 3A). We observed that the VLDL fraction isolated from aortic tissue having advanced lesions contained numerous large, aggregate, lipid particles in addition to VLDLlike particles, and these VLDL-density particles contained numerous unidentified protein bands in addition to identifiable A-I and C apoproteins (data not shown).…”
Section: Characterization Of Lipoprotein-like Particles From Human Plmentioning
confidence: 99%
“…82 This was followed by studies showing the same cellular itinerary for remnants of chylomicrons and VLDL in normal as well as estradioltreated rats 83 and by the isolation and characterization of early and late endosomes and a receptor-recycling compartment from rat livers. 63,84 This work showed clearly that LDL and chylomicron and VLDL-remnants follow a common postendocytic pathway leading to lysosomal catabolism in hepatocytes.I also initiated studies of hepatic lipoprotein catabolism in Watanabe hereditary hyperlipidemic (WHHL) rabbits, homozygous for a mutant LDL receptor that is receptornegative for LDL (but not definitively for cholesterol-rich VLDL containing apoE). These animals are, however, hypertriglyceridemic as well as hypercholesterolemic and we found, together with Brown and Goldstein, that their VLDL (containing apoB-100 and rich in apoE), resemble remnant particles.…”
mentioning
confidence: 99%